Análise do Programa Bolsa Família no Município de Capão Bonito-SP na perspectiva do beneficiário - Cravo, Carla Aparecida (Universidade Federal de São Carlos, 2017)
The present study aims to analyze the impacts of the Bolsa Família Program - PBF, in Capão Bonito-SP, studying the conditions of implementation, maintenance of cadastral data, monitoring of beneficiaries and co-responsibilities. The municipality that is the object of this research has 46,178 inhabitants and the Human Development Index of the City (IBGE, 2010) of 0.721, however, it presented a total annual of 4,814 beneficiary families in 2016, with monthly variations, numbers that demand public policies capable of meeting vulnerabilities stemming from low employability due to economic stagnation and one of the generators of the significant local crime rate. To verify the impacts of the program, we searched the housing, food, health and education conditions through a questionnaire to ascertain the beneficiaries' perceptions regarding the possible improvements brought about by the increase in income and its efficiency in the fight against poverty. The first chapter discusses a history of the origin of social policies in Europe, North and Central America and Africa focusing on their motivations and conceptions according to the needs of the market and society. In the sequence, the Brazilian assistance policies antecedent to the program are contextualized. Chapter 3 deals with the program, its regulations, conditionalities and appropriateness from its implementation in 2004 to the present. The survey questioned how conditionalities affect beneficiaries and whether they favor access to health and education services as described in the PBF configuration. To better understand the study object, the local socioeconomic scenario was characterized, explaining the mechanisms of conditional income transfer programs as public policies to combat poverty. The method of deductive approach was used, characterizing the study as exploratory. The data were collected in a field survey carried out with the PBF cardholders, associating quantitative and qualitative data obtained in the individual questionnaire, semi-structured, directed to the data collection to analyze the effects of this strategic tool of social policy and its approach in the fight poverty and poor income distribution. For the analysis of the data collected, we also used the statistical method that allows better understanding of the considerations of the study.
Analysis of the Bolsa Família Program in the Municipality of Capão Bonito-SP in the beneficiary's perspective
Keywords: Programa Bolsa Família; Programa de Transferência de Renda Condicionada; Pobreza; Pesquisa de avaliação (Programas de ação social); Evaluation research (Social action programs); Poverty; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS; CIENCIAS SOCIAIS APLICADAS